Analisis Perbandingan Kosmologi Hindu dalam Pandangan Sains dan Veda - I Made Bagus Andi Purnomo (Pramana: Jurnal Hasil Penelitian, 2021)
Since the beginning of humans in the world, questions like these actually began to grow and develop. Until now, scientists or people who pursue the field of science focus on understanding the universe and its contents in the form of special science, namely astronomy and cosmology. Understanding astronomy itself is a branch of science that involves observing celestial bodies (such as stars, planets, comets, nebulae, star clusters or galaxies) as well as natural phenomena that occur outside the Earth's atmosphere. Meanwhile, cosmology is understood as a branch of astronomy that studies the origin and evolution of the universe. This study uses a qualitative approach. Sources of data used are primary data sourced from literature/libraries. Data collection techniques were carried out by using library and documentation methods. In this study using data analysis methods with qualitative descriptive techniques. The conclusions that can be presented in this discussion are based on a scientific basis, there are several theories of the creation of the universe such as the big bang theory, steady state theory, nebula theory, planetisimals, cosmic microwave basic radiation theory. Whereas in the Hindu concept there are several theories in various Hindu literature regarding the creation of the universe. In some verses of the Vedic Sruti as in the RigVeda and also the Atharwa Veda. Meanwhile, in the Puranas, the creation of the universe is described in the Bhagavata Purana in which the creation of the universe is divided into two phases. Namely the first phase of the creation of the universe by Visnu/Narayana, the second phase of the creation of the material universe by Lord Brahma who was born from the navel of Vishnu. In addition, in the Balinese lontar, namely Buwana Kosa, the creation of the universe is also narrated. According to this lontar, God is called Bhatara Siwa (Shivaistic). Lord Shiva is transcendent and immanent or impersonal and personal. Lord Shiva is everywhere and at the same time transcends all. Lord Shiva is the source of everything and everything and the place where everything returns.